A CAD-oriented structural topology optimization method. (15th October 2020) - Jiu, Lipeng; Zhang, Weihong; Meng, Liang; Zhou, Ying; Chen, Liang
Highlights: A CAD-oriented topology optimization method has been developed. Two schemes have been proposed for implicit representation of CAD model. Numerical examples have fully demonstrated the validity of the method. The performance of the method has been investigated. Abstract: In this paper, we develop a CAD-oriented topology optimization method incorporating directly the CAD model into the feature-driven optimization (FDO) framework. Practically, any free-form design domain model (FDDM), defined by the CAD model in stereolithography (STL) file format, is first represented by a level set function employing a radial basis function (RBF) interpolation technique. Feature-based topology variation model (TVM) consisting of design and non-design features is then constructed, with the former affording design flexibility whilst the latter preserving the components for engineering requirements. By coupling the FDDM with the TVM via Boolean intersection operation, the topology optimization framework is constructed, and each analysis problem is solved by the finite cell method (FCM). A boundary integral scheme is implemented for efficient sensitivity analysis. It is shown that the developed method shall pose almost no restriction on the expertise of modeling and meshing related to the conventional finite element method. Several examples of increasing complexities are dealt with to demonstrate the effectiveness and the generality of the proposed method.